Fine-mapping genomic loci refines bipolar disorder risk genes - Koromina, Maria; Ravi, Ashvin; Panagiotaropoulou, Georgia; Schilder, Brian M.; Humphrey, Jack; Braun, Alice; Bidgeli, Tim; Chatzinakos, Chris; Coombes, Brandon J.; Kim, Jaeyoung; Liu, Xiaoxi; Terao, Chikashi; et al. (Nature neuroscience, 2025)
Bipolar disorder is a heritable mental illness with complex etiology. While the largest published genome-wide association study identified 64 bipolar disorder risk loci, the causal SNPs and genes within these loci remain unknown. We applied a suite of statistical and functional fine-mapping methods to these loci and prioritized 17 likely causal SNPs for bipolar disorder. We mapped these SNPs to genes and investigated their likely functional consequences by integrating variant annotations, brain cell-type epigenomic annotations, brain quantitative trait loci and results from rare variant exome sequencing in bipolar disorder. Convergent lines of evidence supported the roles of genes involved in neurotransmission and neurodevelopment, including SCN2A, TRANK1, DCLK3, INSYN2B, SYNE1, THSD7A, CACNA1B, TUBBP5, FKBP2, RASGRP1, FURIN, FES, MED24 and THRA among others in bipolar disorder. These represent promising candidates for functional experiments to understand biological mechanisms and therapeutic potential. Additionally, we demonstrated that fine-mapping effect sizes can improve performance of bipolar disorder polygenic risk scores across diverse populations and present a high-throughput fine-mapping pipeline.
Gesehen am 09.09.2025